Implementation of Shortest Path Algorithms - Amruta, Amruta; Sneha Pawar,; Bharati Bhamare, (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
An important area of study that models the relationships between items is called graph theory. The shortest path between two objects is one of the most important concepts in graph theory. Many algorithms, such as Dijkstra's Algorithm, Prim’s Algorithm, Floyd Warshall Algorithm have been created for this purpose.
Keywords: Dijkstra’s Algorithm; Prim’s algorithm; Floyd-Warshall Algorithm; Kruskal’s Algorithm